Pesantren: Kaderisasi Ulama dan Regenerasi Umat - Hasan, Subri (LENTERNAL: Learning and Teaching Journal, 2022)
It is difficult to separate the ritual from the ritual, where the history of the ritual has been rooted in Indonesian society for centuries before Indonesia's independence and even before the Islamic kingdoms were established. The trainers to this day remain independent and honestly exist to organize educational and teaching programs, especially in the field of religion, and their existence inspires the current model and system of education. It is the Book of the Scriptures, and it is the Scripture of the apostles. So the Salafist model trainer can survive and develop over time. The classical scholars concerned with the transmission of the model and curriculum of training that were pioneered decades earlier are historical proof of the progress and greatness of the centuries.